MOTIVASI PENGUNJUNG DESA WISATA BULU CINA KABUPATEN KAMPAR - Aditya Jojor Agustina; Yoskar Kadarisman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Motivation of a person to take a trip is different, in this study according to Krippendorf, 1997, there are 8 indicators that motivate a person to travel, but relating to the tour of Bulu China Tourism Village there are only 4 indicators, namely refreshment motivation, escape, education and fantasy motivation. The research method used in this research is descriptive quantitative method. Data collection is done by distributing questionnaires, interviews, observation and documentation. The technique of determining the sample uses the Slovin formula with a measurement scale that is the Likert scale. The number of samples in this study were 98 samples. The results of this study resulted in refreshment motivation getting a score of 1.275, escape motivation 761 scores, educational motivation of 1.111 scores, fantasy motivation of 1215 scores. Keywords: Motivation, Chinese Reed Tourism Village Kampar District